Immunogenic Properties Studyoffusion Recombinant Proteins Based on VP6 and VP8 of Human Rotavirus A - I. V. Dukhovlinov; E. G. Bogomolova; E. A. Fedorova; A. S. Simbirtsev (Эпидемиология и вакцинопрофилактика, 2015)
Rotavirus infection is the leading cause of severe acute diarrhea among young children worldwide. Contagion with these viruses often leads to severe dehydration of organism. Rotaviral gastroenteritis cases may repeat intra vitam. Because of the absence of drugs with direct action on rotavirus, a timely vaccination is considered the most effective way of this disease's control. Nowadays vaccines based on attenuated alive rotaviral strains are used for this purpose, which can result in different complications. In this work the immunogenicity of recombinant fusion proteins VP6VP8 and FliCVP6VP8 - the crucial active agents of the candidate vaccine against rotaviruses - was studied. As part of the study highly purified proteins preparationsin native state were obtained, their high antigenic activity in experiments with laboratory Balb/c mice was demonstrated.